A STUDY ON T HE ABILITY OF THE FIRST YEAR STUDENTS OF SMK FARMASI IKASARI PEKANBARU IN IDENTIFYING THE USE OF PRONOUNS IN READING TEXT - elizha, Muthia; Azhar, Fadly; ', Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is aimed to describe the level of the first year students’ ability of SMK Farmasi Ikasari Pekanbaru in identifying the use of pronouns in reading text. The design of this research is descriptive research, which has one variable to observe. This research used quantitative data, where the students were assessed by their score. To determine the sample, this research used cluster random sampling technique. The population of this research was X 1 Analisis Kesehatan in the academic year 2016/2017. The total number of population was 306 students. There were 26 students chosen as the samples of this research. The instruments of the research were 40 multiple choice questions. In collecting the data this research used written test and it had to be done in 100 minutes. All of the short stories are taken from English text book and internet. Based on the result of the research, there were 2 students (7.7%) in excellent ability level, 18 students (69.2%) who were in good ability level, 3 students (11.5%) who were in average level. Then, there were 3 students (11.5%) who were in poor level. In other words, the first year students of SMK Farmasi Ikasari Pekanbaru ability level are categorized in average level. Moreover, from the result found, the students’ ability is in average level with the mean score 64.7Key words: student, ability, pronouns, reading text